A photocatalytic composite material, a preparation method and application thereof

CN122955495APending Publication Date: 2026-10-23XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611005716.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]因此,亟须提供一种能够将rGOQDs与ZnIn2S4有效复合,并充分发挥两者协同效应的新型光催化复合材料,以解决现有技术中光生载流子易复合、光催化效率低的技术问题

Benefits of technology

本发明提出一种光催化复合材料及其制备方法与应用,通过将碳基量子点(特别是rGOQDs)负载于硫铟锌(ZnIn2S4)表面,构建了具有紧密异质界面的复合结构;该碳基量子点作为高效的电子受体,能够快速捕获半导体在可见光激发下产生的光生电子,有效抑制光生电子-空穴对在材料内部的复合,大幅延长了光生载流子的寿命;同时,该复合材料保留了ZnIn2S4良好的可见光响应能力和层状结构特性,结合rGOQDs优异的导电性能,显著降低了界面电荷传输阻力,并提高了对有机污染物(如盐酸四环素)的吸附能力和降解效率;此外,该复合材料具有优异的循环稳定性和可重复使用性,解决了现有半导体光催化材料光生载流子易复合、光量子效率低的技术瓶颈,具有广泛的工业应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955495A_ABST
    Figure CN122955495A_ABST
Patent Text Reader

Abstract

The application discloses a kind of photocatalytic composite materials and its preparation method and application, belong to photocatalytic technical field;To solve the problem that ZnIn2S4 photo-generated carrier is easily compounded, reduced graphene oxide quantum dots (rGOQDs) are loaded on the surface of flower-like ZnIn2S4 by hydrothermal method, and a composite catalyst is constructed;As electron acceptor, rGOQDs effectively inhibit carrier recombination and reduce interface charge transport resistance, and the photocatalytic efficiency is improved by band matching mechanism;Experiments show that the degradation rate of tetracycline hydrochloride by the composite material with a loading amount of 2wt% under visible light irradiation for 60min is 77.1%, and the cyclic stability is excellent;The application is suitable for efficient degradation of water organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of nanomaterials and photocatalysis, specifically to a photocatalytic composite material, its preparation method, and its application. Background Technology

[0002] In recent years, with the rapid development of industrialization and agricultural modernization, a large amount of organic pollutants, represented by antibiotics, have continuously entered water bodies. Antibiotic pollutants, due to their environmental persistence, biotoxicity, and tendency to induce the spread of drug resistance genes, have become a critical problem urgently needing to be solved in the field of water pollution control. Traditional methods such as physical adsorption and biodegradation generally suffer from low treatment efficiency, high operating costs, and the potential for secondary pollution when treating structurally stable and difficult-to-biodegrade antibiotic pollutants. Photocatalysis, as an advanced oxidation technology that utilizes solar energy to drive redox reactions, offers advantages such as mild reaction conditions and no secondary pollution, and has received widespread attention in the field of environmental remediation.

[0003] Among numerous semiconductor photocatalytic materials, zinc indium sulfide (ZnIn2S4) is a typical ternary metal sulfide semiconductor with a narrow bandgap (approximately 2.3~2.7 eV), enabling it to effectively respond to the visible light region. It also possesses a unique layered crystal structure, providing a large specific surface area and abundant surface active sites, showing promising application prospects in the photocatalytic degradation of organic pollutants. However, under photoexcitation, the photogenerated electrons and holes generated within pure-phase ZnIn2S4 readily recombine rapidly in the bulk phase or on the surface, leading to a significant reduction in the number of effective charge carriers participating in photocatalytic redox reactions and a marked decrease in quantum efficiency, severely limiting its photocatalytic performance in practical applications.

[0004] How to effectively suppress photogenerated carrier recombination in ZnIn2S4 and improve its interfacial charge separation efficiency and photocatalytic activity has become an important research direction for ZnIn2S4-based photocatalytic materials. Currently, constructing heterojunctions, element doping, or compositing with carbon nanomaterials are relatively effective modification strategies. Among them, carbon-based nanomaterials (such as reduced graphene oxide quantum dots, rGOQDs) combine the size effect of quantum dots with the excellent conductivity of graphene and have abundant edge defect sites, which are expected to act as electron acceptors to rapidly capture photogenerated electrons.

[0005] Therefore, there is an urgent need to provide a novel photocatalytic composite material that can effectively combine rGOQDs with ZnIn2S4 and fully leverage their synergistic effect, in order to solve the technical problems of easy recombination of photogenerated carriers and low photocatalytic efficiency in the existing technology. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a photocatalytic composite material, its preparation method and application.

[0007] To achieve the above objectives, the present invention provides the following technical solution: This application provides a photocatalytic composite material, characterized in that it comprises: A semiconductor body comprising a ternary metal sulfide having a layered crystal structure; and Carbon-based quantum dots are loaded onto the surface of the semiconductor substrate, forming a heterogeneous interface with the semiconductor substrate. The carbon-based quantum dot can receive photogenerated electrons generated by the semiconductor host under photoexcitation, thereby suppressing the recombination of photogenerated electron-hole pairs.

[0008] Preferably, the ternary metal sulfide is zinc indium sulfide (ZnIn2S4), which has a hexagonal crystal structure and is formed by the self-assembly of two-dimensional nanosheets into a flower-like microsphere structure.

[0009] Preferably, the carbon-based quantum dots are reduced graphene oxide quantum dots (rGOQDs), the particle size of the reduced graphene oxide quantum dots is 8-10 nm, and the mass fraction of the reduced graphene oxide quantum dots in the photocatalytic composite material is 1 wt% to 3 wt%.

[0010] A method for preparing the photocatalytic composite material as described above includes the following steps: Step S1: Disperse carbon-based quantum dots in a solvent to prepare a carbon-based quantum dot dispersion; Step S2: The precursor of the ternary metal sulfide is added to the carbon-based quantum dot dispersion, and after mixing, a solvothermal reaction is carried out to generate the ternary metal sulfide in situ and load it onto the surface of the carbon-based quantum dots to obtain a photocatalytic composite material.

[0011] Preferably, the carbon-based quantum dots in step S1 are obtained by reducing graphene oxide; the reduction treatment includes: dispersing graphene oxide in water, adjusting the pH to alkaline, carrying out a hydrothermal reduction reaction at 180-220°C for 12-36 hours, and obtaining the carbon-based quantum dots after purification.

[0012] Preferably, in step S2, the precursor of the ternary metal sulfide includes a zinc source, an indium source, and a sulfur source; The zinc source is zinc chloride, the indium source is indium trichloride tetrahydrate, and the sulfur source is thioacetamide; the solvothermal reaction is carried out at a temperature of 150-180°C for 10-14 hours.

[0013] Application of a photocatalytic composite material as described above in the degradation of organic pollutants in water.

[0014] Preferably, the optical bandgap of the semiconductor substrate is determined by the Tauc formula, which is: in, The absorption coefficient is... Photon energy, is the intrinsic constant of the photocatalyst. For the no-bandwidth, It depends on the type of bandgap of the semiconductor: when the semiconductor has a direct bandgap, n=1 / 2; when the semiconductor has an indirect bandgap, n=2.

[0015] Preferably, the photocatalytic degradation process of organic pollutants by the photocatalytic composite material conforms to a pseudo-first-order reaction kinetic model, and its kinetic equation is: in, This represents the initial concentration of the organic pollutant solution. Reaction time The concentration of organic pollutants in the solution at any given time. The kinetic rate constant for a pseudo-first-order reaction is... This refers to the reaction time.

[0016] Preferably, the valence band potential (EVB) and conduction band potential (ECB) of the semiconductor host satisfy the following band structure relationship: The conduction band potential ECB is calculated according to the formula ECB=EVB. Eg is calculated, where E g The bandgap width of the semiconductor body; The valence band potential EVB is determined by the band structure calculation formula, which is as follows: ENHE / V= +EVB-XPS-4.44 in, The work function of the instrument. =4.5, EVB XPS is the valence band binding energy measured by X-ray photoelectron spectroscopy (XPS), and ENHE is the potential relative to the standard hydrogen electrode.

[0017] Compared with the prior art, this application has the following beneficial effects: This invention proposes a photocatalytic composite material, its preparation method, and its applications. By loading carbon-based quantum dots (especially rGOQDs) onto the surface of zinc indium sulfide (ZnIn2S4), a composite structure with a tight heterogeneous interface is constructed. These carbon-based quantum dots, acting as efficient electron acceptors, can rapidly capture photogenerated electrons generated by semiconductors under visible light excitation, effectively suppressing the recombination of photogenerated electron-hole pairs within the material and significantly extending the lifetime of photogenerated carriers. Simultaneously, this composite material retains the excellent visible light response and layered structure characteristics of ZnIn2S4, and combined with the superior conductivity of rGOQDs, significantly reduces interfacial charge transport resistance and improves the adsorption capacity and degradation efficiency of organic pollutants (such as tetracycline hydrochloride). Furthermore, this composite material exhibits excellent cycle stability and reusability, overcoming the technical bottlenecks of easy recombination of photogenerated carriers and low quantum efficiency in existing semiconductor photocatalytic materials, and has broad industrial application prospects. Attached Figure Description

[0018] Figure 1 This is a high-resolution transmission electron microscope (HRTEM) image of reduced graphene oxide quantum dots (rGOQDs) in an embodiment of the present invention. Figure 2 The XRD patterns of graphene oxide (GO) and reduced graphene oxide (RGO) in the embodiments of the present invention are shown. Figure 3 The XRD patterns of rGOQD / ZnIn2S4 composite materials with different rGOQD loadings and pure ZnIn2S4 are shown in the embodiments of the present invention. Figure 4 The Raman spectra of RGO, pure ZnIn2S4 and RC-2 samples in the embodiments of the present invention are shown below. Figure 5 These are scanning electron microscope (SEM) images of pure ZnIn2S4, RC-1, RC-2 and RC-3 samples in the embodiments of the present invention; Figure 6 The EDS energy spectrum and elemental distribution (S, In, Zn, C, O) of the RC-2 sample in this embodiment of the invention are shown. Figure 7 These are transmission electron microscope (TEM) images and high-resolution transmission electron microscope (HRTEM) images of the RC-2 sample in the embodiments of the present invention; Figure 8 The UV-Vis diffuse reflectance spectra (UV-visDRS) of pure ZnIn2S4 and composite materials with different rGOQDs loadings in the embodiments of the present invention are shown. Figure 9 (ahv) is the sample in the embodiment of the present invention. 2 -hvTauc curve (used to estimate bandgap width); Figure 10 The images show the photoluminescence (PL) spectra of pure ZnIn2S4 and composite materials with different rGOQDs loadings in the embodiments of the present invention. Figure 11 The transient photocurrent response curves of pure ZnIn2S4 and composite materials with different rGOQDs loadings in the embodiments of the present invention are shown. Figure 12 The image shows the electrochemical impedance spectroscopy (EIS) spectra of pure ZnIn2S4 and composite materials with different rGOQDs loadings in the embodiments of the present invention. Figure 13 The UV-Vis absorption spectra of pure ZnIn2S4 and composite materials with different rGOQDs loadings degrading tetracycline hydrochloride over time are shown in the embodiments of the present invention (a is ZnIn2S4, b is RC-1, c is RC-2, d is RC-3). Figure 14 The photocatalytic degradation rate curves (a) and degradation rate bar charts (b) of different samples for tetracycline hydrochloride in the embodiments of the present invention are shown. Figure 15 This is a first-order kinetic fitting curve of the degradation of tetracycline hydrochloride by pure ZnIn2S4 and composite materials with different rGOQDs loadings in the embodiments of the present invention. Figure 16 The following are the cycle stability test curves (a) and XRD comparison diagrams (b) of the RC-2 sample degrading tetracycline hydrochloride in the embodiments of the present invention; Figure 17 The Tauc bandgap diagram (a) and VB-XPS spectrum (b) of ZnIn2S4 in this embodiment of the invention are shown. Figure 18 This is a schematic diagram of the photocatalytic reaction mechanism of the rGOQD / ZnIn2S4 composite photocatalyst material in an embodiment of the present invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Furthermore, in this invention, an element referred to as fixed to or disposed on another element may be directly disposed on the other element, or there may be an intermediate element. When an element is considered to be connected to another element, it may be directly connected to the other element, or there may be an intermediate element present simultaneously. The terms vertical, horizontal, left, right, and similar expressions used herein are for illustrative purposes only and do not represent the only possible implementation.

[0021] Example 1 This embodiment describes in detail the preparation of reduced graphene oxide quantum dots (rGOQDs): Concentrated sulfuric acid and concentrated phosphoric acid were mixed at a volume ratio of 9:1 (total volume 200 mL, including 180 mL of concentrated sulfuric acid and 20 mL of concentrated phosphoric acid). 1.5 g of graphite flakes were added to the mixture. Then, while stirring continuously, 9.0 g of potassium permanganate (KMnO4) was slowly added to the mixture in batches of 1.5 g each, which produced a slight exothermic reaction.

[0022] After the addition of materials is complete, the mixture is heated to 50°C in a water bath and stirred continuously for 8 hours.

[0023] After the reaction was completed, 400 mL of ice water was added to the system to terminate the reaction, and then hydrogen peroxide (H2O2) was used to titrate until the mixture turned bright yellow.

[0024] Subsequently, the pH of the suspension was adjusted to 8 using sodium hydroxide (NaOH) solution. The pH-adjusted suspension was transferred to a hydrothermal reactor and hydrothermally treated at 200°C for 24 hours. After the reactor cooled to room temperature, the resulting product was filtered through a 0.22 μm microporous membrane to remove large black precipitates, and the filtrate was collected. The filtrate was concentrated using a rotary evaporator and then dialyzed using an MD44-1000 dialysis bag to remove impurity ions. After dialysis, the filtrate was freeze-dried to obtain reduced graphene oxide quantum dots (rGOQDs) powder.

[0025] The resulting rGOQDs typically have a particle size of 8-10 nm, such as Figure 1 As shown, the lattice fringes of its (002) crystal plane can be clearly observed by high-resolution transmission electron microscopy, and the interplanar spacing is about 0.337 nm (i.e. 3.37 Å).

[0026] Example 2 This embodiment describes in detail the preparation of flower-shaped zinc indium sulfide (ZnIn2S4): Flower-shaped ZnIn2S4 was synthesized via a hydrothermal method using zinc chloride (ZnCl2), indium trichloride tetrahydrate (InCl3·4H2O), and thioacetamide (TAA) as precursors.

[0027] The specific steps are as follows: Dissolve 0.0682g (0.5mmol) of ZnCl2, 0.2932g (1mmol) of InCl3·4H2O and 0.30g (4mmol) of thioacetamide in 50mL of distilled water and stir magnetically for 30 minutes at room temperature.

[0028] The mixed solution was then transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and heated at 160 °C for 12 hours.

[0029] After the reaction was completed, the sample was naturally cooled to room temperature, washed several times by centrifugation with anhydrous ethanol and distilled water, and finally dried in an oven at 70°C for 6 hours to obtain pure ZnIn2S4 in the form of a bright yellow powder.

[0030] Example 3 This embodiment describes in detail the preparation of the rGOQD / ZnIn2S4 composite photocatalytic material: The rGOQDs prepared in Example 1 were prepared into a dispersion of known concentration using deionized water.

[0031] According to the mass ratios of rGOQDs to the theoretical yield of ZnIn2S4 of 1%, 2%, and 3%, respectively, the corresponding volumes of rGOQDs dispersions were measured and added to beakers.

[0032] Subsequently, 0.0682 g ZnCl2, 0.2932 g InCl3·4H2O and 0.30 g thioacetamide were dissolved in 50 mL of the above rGOQDs aqueous dispersion.

[0033] After stirring at room temperature, the mixture was sonicated for 30 minutes to ensure that the carbon-based quantum dots were fully dispersed in the solution. The mixture was then transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and heated at 160 °C for 12 hours.

[0034] After the reaction was completed, the sample was cooled to room temperature, washed several times by centrifugation with anhydrous ethanol and distilled water, and finally dried in an oven at 70°C for 6 hours to obtain yellow or yellow-green rGOQD / ZnIn2S4 composite materials with different rGOQD loadings, which were labeled as RC-1, RC-2 and RC-3, respectively.

[0035] Example 4 This embodiment provides a detailed description of the structure and morphology characterization of the photocatalytic composite material: In this embodiment, the prepared sample was characterized in terms of phase, microstructure and elemental distribution.

[0036] like Figure 2 and Figure 3 As shown, the phase composition and crystal structure of the sample were analyzed using X-ray diffraction (XRD).

[0037] Figure 2 In the study, graphene oxide (GO) exhibited a sharp (001) diffraction peak at 2θ = 10.2°, corresponding to an interlayer spacing of approximately 0.85 nm. After hydrothermal reduction, this peak of RGO disappeared, while a broadened (002) diffraction peak appeared at 2θ ≈ 24.5°, confirming the effective reduction of GO.

[0038] Figure 3 The results show that all ZnIn2S4-based samples exhibit characteristic diffraction peaks at 2θ values ​​of 21.5°, 27.7°, 47.2°, 52.3°, and 56.1°, corresponding to the (006), (102), (110), (116), and (202) crystal planes of hexagonal ZnIn2S4, respectively. This is highly consistent with the standard card (PDF#65-2023), and the introduction of rGOQDs did not change the crystal structure of ZnIn2S4.

[0039] like Figure 4 The Raman spectra of pure ZnIn2S4 show that at 72, 94, 246, and 348 cm⁻¹, the light intensity is high. - A characteristic peak appears near ¹, with RGO at 1348 cm⁻¹. - ¹ and 1602cm - ¹D and G bands are present, while in the composite sample RC-2, the D / G bands of carbon exhibit a redshift, confirming that a heterogeneous interface with close electronic interactions is formed between rGOQDs and ZnIn2S4.

[0040] like Figure 5 As shown by scanning electron microscopy (SEM), pure ZnIn2S4 exhibits a three-dimensional flower-like microsphere structure composed of numerous smooth nanosheets self-assembled. The overall flower-like structure of the RC-1 sample remains intact, while the surface of the nanosheets becomes roughened. The surface roughness of the nanosheets in RC-2 further increases, and the flower-like structure is basically preserved. However, when the doping concentration reaches 3wt%, the flower-like structure of RC-3 is destroyed due to the aggregation of rGOQDs, and the surface is over-coated.

[0041] Combination Figure 6 EDS energy dispersive spectroscopy analysis showed that C, O, Zn, In and S elements were uniformly distributed in the RC-2 sample, with the following weight percentages (wt%): C 16.25%, O 2.22%, S 23.66%, Zn 18.23%, and In 39.64%, respectively, confirming the successful composite and good dispersion of rGOQDs in the composite material.

[0042] Using transmission electron microscopy (TEM) Figure 7TEM and HRTEM observations showed that rGOQDs were uniformly anchored on the surface of thin tuft nanosheets in low-magnification TEM; in high-resolution HRTEM, 0.32 nm lattice fringes belonging to the ZnIn2S4(102) crystal plane and 0.336 nm lattice fringes belonging to the rGOQD(002) crystal plane could be clearly observed to coexist in the same field of view, which strongly corroborates the successful composite of the two.

[0043] Example 5 This embodiment describes the photoelectrochemical performance testing and band gap determination of photocatalytic composite materials: This embodiment systematically tested the light absorption performance and photogenerated carrier separation behavior of the sample.

[0044] like Figure 8 As shown in the UV-Vis DRS, all samples exhibit significant absorption in the visible region, with the absorption edge approximately between 450-550 nm.

[0045] This invention utilizes the Tauc formula to determine the bandgap width of materials ( The formula is as follows: In the formula, The absorption coefficient is... Let A be the photon energy, and A be the intrinsic constant of the photocatalyst. The bandgap width is n, which depends on the type of bandgap in the semiconductor (n=1 / 2 for direct bandgap and n=2 for indirect bandgap).

[0046] pass Figure 9 The band gap of pure ZnIn2S4 was determined to be approximately 2.52 eV by extrapolation.

[0047] After the introduction of rGOQDs, the absorption edge of RC-1 redshifts, while the band gaps of RC-2 and RC-3 slightly increase, indicating that an appropriate amount of rGOQDs can broaden the optical response range, but excessive loading may lead to light shading effect.

[0048] pass Figure 10 Photoluminescence (PL) spectra were used to assess the recombination of photogenerated carriers. Under 330 nm excitation conditions, the luminescence intensity of each sample was in the following order: pure ZnIn2S4 > RC-1 > RC-3 > RC-2, indicating that RC-2 had the strongest inhibitory effect on electron-hole recombination.

[0049] pass Figure 11 The transient photocurrent response curve (It) and Figure 12The interfacial charge transport performance was tested by electrochemical impedance spectroscopy (EIS). The results showed that the RC-2 sample had the strongest photocurrent response and the smallest impedance semicircle radius, exhibiting the best charge separation efficiency and the lowest interfacial transport resistance. The photocurrent magnitude order was RC-2>RC-3>RC-1>pure ZnIn2S4.

[0050] Example 6 This embodiment describes the performance evaluation and kinetic analysis of photocatalytic degradation as follows: Using tetracycline hydrochloride (TC-HCl) as a model pollutant, the photocatalytic performance of each sample was evaluated under visible light irradiation.

[0051] Figure 13 The study showed the changes in the UV absorption spectra of different samples during the degradation of tetracycline hydrochloride over time. As the irradiation time increased, the intensity of the characteristic absorption peak of the pollutant gradually decreased.

[0052] After 60 minutes of light exposure, as Figure 14 As shown, the degradation rate of pure ZnIn2S4 by TC-HCl was 65.5%, RC-1 was 70.8%, RC-2 reached 77.1%, and RC-3 was 74.5%, with RC-2 showing the best degradation rate.

[0053] This invention uses a pseudo-first-order reaction kinetic model to fit the degradation process, and its kinetic equation is as follows: ,in This represents the initial concentration of the tetracycline hydrochloride solution. Reaction time Concentration at time, The kinetic rate constant for a pseudo-first-order reaction is... This refers to the reaction time.

[0054] Figure 15 The fitting results show that the rate constants k for ZnIn2S4, RC-1, RC-2, and RC-3 are 0.00532, 0.00729, 0.00908, and 0.00775 min, respectively. - ¹, among which RC-2 has the largest k value, further confirming its optimal photocatalytic performance.

[0055] In addition, RC-2 was subjected to four cycles of degradation experiments (e.g. Figure 16 As shown in a), the degradation rate remained at around 70% after four cycles; the XRD pattern of the sample after the reaction (as shown in a) Figure 16 (b) The characteristic peaks did not shift or attenuate, indicating that the composite material of the present invention has excellent chemical stability and reusability.

[0056] Example 7 This embodiment describes the band structure calculation and photocatalytic mechanism analysis as follows: This embodiment provides an in-depth analysis of the photocatalytic enhancement mechanism of composite materials: pass Figure 17 The valence band binding energy (EVB) of ZnIn2S4 was obtained by VB-XPS testing. XPS), and then use the band structure calculation formula: ENHE / V= +EVB-XPS-4.44 Convert it to the standard hydrogen electrode (NHE) potential, where The work function of the XPS instrument (in this embodiment) =4.5), where ENHE is the potential relative to the standard hydrogen electrode.

[0057] The calculated valence band potential EVB of ZnIn2S4 is 1.78V.

[0058] Based on the bandgap Eg calculated using the Tauc formula in Example 5, which is 2.52 eV, and according to the fundamental formula for semiconductor band structure: ECB = EVB For example, the calculated conduction band potential ECB of ZnIn2S4 is -0.74V.

[0059] Based on the above band structure parameters, this invention proposes the following... Figure 18 The photocatalytic mechanism shown is as follows: Under visible light irradiation, the valence band electrons of ZnIn2S4 transition to the conduction band (-0.74V). Due to the excellent electronic conductivity of rGOQDs, the conduction band electrons rapidly migrate to the surface of rGOQDs, realizing the spatial separation of electrons and holes.

[0060] Electrons migrating to the surface react with adsorbed O2 to generate superoxide radicals (·O2). - Holes remaining in the ZnIn2S4 valence band (1.78V) can oxidize H2O / OH. - Hydroxyl radicals (·OH) are generated.

[0061] These active species work synergistically to gradually degrade tetracycline hydrochloride into small molecule products such as CO2 and H2O, achieving highly efficient photocatalytic removal of organic pollutants in water.

[0062] In summary, through the above embodiments, this invention fully discloses the preparation method, material structure, photoelectric properties, degradation effect and mechanism of action of rGOQD / ZnIn2S4 photocatalytic composite material.

[0063] The photocatalytic composite material described in this invention utilizes the efficient electron transport capability of carbon-based quantum dots to effectively solve the problem of easy recombination of photogenerated charge carriers in ZnIn2S4, significantly improving the performance of photocatalytic degradation of organic pollutants in water and showing broad prospects for industrial application.

[0064] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0065] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A photocatalytic composite material, characterized in that, include: A semiconductor substrate comprising a ternary metal sulfide having a layered crystal structure; as well as Carbon-based quantum dots are loaded onto the surface of the semiconductor substrate, forming a heterogeneous interface with the semiconductor substrate. The carbon-based quantum dot can receive photogenerated electrons generated by the semiconductor host under photoexcitation, thereby suppressing the recombination of photogenerated electron-hole pairs.

2. The photocatalytic composite material according to claim 1, characterized in that, The ternary metal sulfide is zinc indium sulfide (ZnIn2S4), which has a hexagonal crystal structure and is formed by the self-assembly of two-dimensional nanosheets into a flower-like microsphere structure.

3. The photocatalytic composite material according to claim 1, characterized in that, The carbon-based quantum dots are reduced graphene oxide quantum dots (rGOQDs), the particle size of the reduced graphene oxide quantum dots is 8-10 nm, and the mass fraction of the reduced graphene oxide quantum dots in the photocatalytic composite material is 1 wt% to 3 wt%.

4. A method for preparing a photocatalytic composite material as described in any one of claims 1 to 3, characterized in that, Includes the following steps: Step S1: Disperse carbon-based quantum dots in a solvent to prepare a carbon-based quantum dot dispersion; Step S2: The precursor of the ternary metal sulfide is added to the carbon-based quantum dot dispersion, and after mixing, a solvothermal reaction is carried out to generate the ternary metal sulfide in situ and load it onto the surface of the carbon-based quantum dots to obtain a photocatalytic composite material.

5. The method according to claim 4, characterized in that, The carbon-based quantum dots in step S1 are obtained by reducing graphene oxide; the reduction process includes: dispersing graphene oxide in water, adjusting the pH to alkaline, carrying out a hydrothermal reduction reaction at 180-220°C for 12-36 hours, and obtaining the carbon-based quantum dots after purification.

6. The method according to claim 4, characterized in that, In step S2, the precursor of the ternary metal sulfide includes a zinc source, an indium source, and a sulfur source; The zinc source is zinc chloride, the indium source is indium trichloride tetrahydrate, and the sulfur source is thioacetamide; the solvothermal reaction is carried out at a temperature of 150-180°C for 10-14 hours.

7. The application of a photocatalytic composite material as described in any one of claims 1 to 3 in the degradation of organic pollutants in water.

8. The photocatalytic composite material according to claim 1, characterized in that, The optical bandgap of the semiconductor substrate is determined by the Tauc formula, which is: in, The absorption coefficient is... Photon energy, is the intrinsic constant of the photocatalyst. For the no-bandwidth, It depends on the bandgap type of the semiconductor: When the semiconductor has a direct bandgap, n = 1 / 2; when the semiconductor has an indirect bandgap, n = 2.

9. The photocatalytic composite material according to claim 1, characterized in that, The photocatalytic degradation process of organic pollutants by the photocatalytic composite material conforms to a pseudo-first-order reaction kinetic model, and its kinetic equation is as follows: in, This represents the initial concentration of the organic pollutant solution. Reaction time The concentration of organic pollutants in the solution at any given time. The kinetic rate constant for a pseudo-first-order reaction is... This refers to the reaction time.

10. The photocatalytic composite material according to claim 1, characterized in that, The valence band potential (EVB) and conduction band potential (ECB) of the semiconductor host satisfy the following band structure relationship: The conduction band potential ECB is calculated according to the formula ECB=EVB. Eg is calculated, where E g The bandgap width of the semiconductor body; The valence band potential EVB is determined by the band structure calculation formula, which is as follows: ENHE / V= +EVB-XPS-4.44 in, The work function of the instrument. =4.5, EVB XPS is the valence band binding energy measured by X-ray photoelectron spectroscopy (XPS), and ENHE is the potential relative to the standard hydrogen electrode.